2014
DOI: 10.5812/ircmj.11894
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Nurse Association Perception of Patient Safety Culture

Abstract: Background:In recent decades, patient safety has become a high priority health system issue, due to the high potential of occurring adverse events in health facilities.Objectives:This study was aimed to survey patient safety culture in 2 Iranian educational hospitals.Materials and Methods:In a descriptive, cross-sectional survey, a hospital survey on patient safety culture, was used in two teaching hospitals in Yazd, Iran during 2012. Study population was comprised of the same hospitals' nurses. Stratified-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 15 publications
2
28
2
3
Order By: Relevance
“…Like previous studies, all patient safety culture elements showed positive correlations with each other with one exception: there was no relationship between "frequency of events" and "management support," "teamwork within units," "teamwork across," "staffing, handoffs transitions" and "non-punitive responses" (29)(30)(31). similar to previous studies, "staffing" scored the lowest among all the patient safety culture elements (28) and "teamwork within units" (32,33) scored the highest in this study. Patient safety cultures within hospitals still require development.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Like previous studies, all patient safety culture elements showed positive correlations with each other with one exception: there was no relationship between "frequency of events" and "management support," "teamwork within units," "teamwork across," "staffing, handoffs transitions" and "non-punitive responses" (29)(30)(31). similar to previous studies, "staffing" scored the lowest among all the patient safety culture elements (28) and "teamwork within units" (32,33) scored the highest in this study. Patient safety cultures within hospitals still require development.…”
Section: Discussionsupporting
confidence: 66%
“…This study has demonstrated the presence of a moderate patient safety culture (64.7%) that is both lower (27) and higher than other studies (28). In contrast to other studies, this study (29) revealed no significant relationship between staff members' years of service and patient safety culture ratings.…”
Section: Discussioncontrasting
confidence: 55%
“…and the study of Karaca & Arslan of nurses working in a private hospital using the same scale 14,15. A study conducted on 302 nurses working in the university hospitals in Iran, and a study conducted on 463 nurses in China indicated that patient safety perceptions of nurses weren’t at the desired level 4,5…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a need by healthcare managers for continuous measurement of patient safety to detect any weaknesses and to correct them before causing adverse events (Bahrami et al. ). Also, there should be better coordination between hospital's units during shift changes regarding important information about patient care to improve handsoff and transition of care (Morello et al.…”
Section: Implications For Nursing and Health Policymentioning
confidence: 99%
“…Nurses who had specific education about patient safety showed significant improvements in the 'frequency of events reported' and in 'non-punitive response to error' (AbuAlRub & Abu Alhijaa 2014). In addition, there is a need by healthcare managers for continuous measurement of patient safety to detect any weaknesses and to correct them before causing adverse events (Bahrami et al 2014). Also, there should be better coordination between hospital's units during shift changes regarding important information about patient care to improve handsoff and transition of care (Morello et al 2013;Woodthorpe et al 2013).…”
Section: Implications For Nursing and Health Policymentioning
confidence: 99%